A Critical Role of Sodium Flux via the Plasma Membrane Na+/H+ Exchanger SOS1 in the Salt Tolerance of Rice. Issue 2 (16th April 2019) - El Mahi, Houda; Pérez-Hormaeche, Javier; De Luca, Anna; Villalta, Irene; Espartero, Joaquín; Gámez-Arjona, Francisco; Fernández, José Luis; Bundó, Mireia; Mendoza, Imelda; Mieulet, Delphine; Lalanne, Eric; Lee, Sang-Yeol; et al.
Abstract : The plasma membrane Na + /H + exchanger SOS1 plays a major role in the salt tolerance of rice by controlling Na + uptake and root-shoot partitioning. Abstract: Rice ( Oryza sativa ) stands among the world's most important crop species. Rice is salt sensitive, and the undue accumulation of sodium ions (Na + ) in shoots has the strongest negative correlation with rice productivity under long-term salinity. The plasma membrane Na + /H + exchanger protein Salt Overly Sensitive 1 (SOS1) is the sole Na + efflux transporter that has been genetically characterized to date. Here, the importance of SOS1-facilitated Na + flux in the salt tolerance of rice was analyzed in a reverse-genetics approach. A sos1 loss-of-function mutant displayed exceptional salt sensitivity that was correlated with excessive Na + intake and impaired Na + loading into the xylem, thus indicating that SOS1 controls net root Na + uptake and long-distance Na + transport to shoots. The acute Na + sensitivity of sos1 plants at low NaCl concentrations allowed analysis of the transcriptional response to sodicity stress without effects of the osmotic stress intrinsic to high-salinity treatments. In contrast with that in the wild type, sos1 mutant roots displayed preferential down-regulation of stress-related genes in response to salt treatment, despite the greater intensity of stress experienced by the mutant. These results suggest there is impaired stress detection or an inability to mount a comprehensive response to salinity in sos1 . In summary, the plasma membrane Na + /H + exchanger SOS1 plays a major role in the salt tolerance of rice by controlling Na + homeostasis and possibly contributing to the sensing of sodicity stress.